2013
DOI: 10.1021/cm4016222
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Transport Mechanisms in Antiperovskite Li3OCl and Li3OBr Superionic Conductors

Abstract: We investigate phase stability and ionic transport mechanisms in two recently discovered superionic conductors, Li 3 OX (X = Cl, Br), from first principles. These compounds, which have an antiperovskite crystal structure, have potential applications as solid electrolytes in Li-ion batteries. We identify a low-barrier three-atom hop mechanism involving Li interstitial dumbbells. This hop mechanism is facile within the (001) crystallographic planes of the perovskite crystal structure and is evidence for the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
255
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(297 citation statements)
references
References 44 publications
40
255
1
1
Order By: Relevance
“…It is, however, predicted to have a positive formation energy relative to a two-phase mixture of LiCl and Li 2 O 2,3 . Furthermore, to ensure a high concentration of diffusion mediating defects, the compound must be synthesized with a composition that deviates from perfect stoichiometry as the energy to form Frenkel pairs in the stoichiometric compound is too high to generate a sufficient number of Li interstitials and vacancies at room temperature 3 . A deeper understanding of the factors responsible for the observed stability of Li 3 OCl is therefore desirable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is, however, predicted to have a positive formation energy relative to a two-phase mixture of LiCl and Li 2 O 2,3 . Furthermore, to ensure a high concentration of diffusion mediating defects, the compound must be synthesized with a composition that deviates from perfect stoichiometry as the energy to form Frenkel pairs in the stoichiometric compound is too high to generate a sufficient number of Li interstitials and vacancies at room temperature 3 . A deeper understanding of the factors responsible for the observed stability of Li 3 OCl is therefore desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Li 3 OCl has a perovskite crystal structure, but with the role of anions and cations reversed ( Figure 1a): The positively charged Li ions form the corner sharing octahedra while the negatively charged O ions occupy the center of the Li-octahedra; the negatively charged Cl occupy the large cages at the center of the unit cell coordinated by 12 Li ions. Several first-principles studies of Li transport in the anti-perovskite crystal structure have predicted low migration barriers for Li-vacancy exchanges, with values on the order of 350 meV 2,3 . An even lower migration barrier of approximately 160 meV was predicted for an interstitial dumbbell mechanism 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al 131 reported the room temperature ionic conductivities for two samples, 0.85 mS cm − 1 for Li 3 OCl with Following the experimental work, Zhang et al 132 proved that Li vacancies and anion sublattice disorder are the driving forces for Li + diffusion in antiperovskites using AIMD simulations. Emly et al 133 later identified a low-barrier three-atom hopping mechanism involving Li interstitial dumbbells, for which the barriers calculated using NEB methods are ∌ 170 meV (Figure 13), 50% lower compared with those of vacancy-driven migration. However, defect formation energy calculations suggest that a high Li interstitial concentration can only be obtained by off-stoichiometry synthesis.…”
Section: Ox Antiperovskitesmentioning
confidence: 99%